2019
DOI: 10.1136/bmjopen-2019-030001
|View full text |Cite
|
Sign up to set email alerts
|

Sense of coherence and physical health–related quality of life in Italian chronic patients: the mediating role of the mental component

Abstract: ObjectiveTo examine the relationship between sense of coherence (SOC) and physical health–related quality of life in patients with chronic illnesses by focusing on the mediating role of the mental component of quality of life.DesignCross-sectional survey design.SettingSecondary care; three departments of an Italian university hospital.MethodsThe participants (n=209) in the study were adult (≥18 years) outpatients with a chronic pathology (eg, diabetes, thyroid disorders or cancer) at any phase in the care traj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
23
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 35 publications
7
23
0
3
Order By: Relevance
“…We found that OA-treatment-specific QoL scores were associated with better internal resources, as measured by the SOC scale [45]. In our study, the self-management domain was correlated with the results from the SOC's comprehensibility subscale.…”
Section: Discussionsupporting
confidence: 57%
“…We found that OA-treatment-specific QoL scores were associated with better internal resources, as measured by the SOC scale [45]. In our study, the self-management domain was correlated with the results from the SOC's comprehensibility subscale.…”
Section: Discussionsupporting
confidence: 57%
“…For example, Galletta et al. ( 2019) examined the mediation effect of mental health between sense of coherence and physical HRQoL in 209 people with chronic diseases. They found that despite a nonsignificant direct association between sense of coherence and physical HRQoL, the indirect effect of the independent variable on HRQoL through mental health was significant.…”
Section: Discussionmentioning
confidence: 99%
“…Mediating roles of mental health in relationships between psychological factors and sleep problems/HRQoL have been reported (Galletta et al., 2019; Holtge et al., 2019; Pavlova et al., 2017). However, to the best of our knowledge, such investigations have never been studied among patients with COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a study, mental health status had a mediating role between physical illnesses and individuals' perceptions of well-being (Lorem et al 2017). Besides, Galletta et al (2019) reported a relationship between mental and physical QoL and the mediating role of mental QoL in the relationship between a psychological construct, i.e., a sense of coherence with physical QoL.…”
Section: Introductionmentioning
confidence: 99%